Cryptic speciation: distinguishing serpentine affiliated sister species Navarretia paradoxiclara and N. paradoxinota from N. intertexta (Polemoniaceae) - Johnson, Leigh A.; Gowen, David; Jensen, Angela B. (Phytotaxa, 2013)
Two species endemic to California in the western United States, Navarretia paradoxiclara and N. paradoxinota, are here described. Both species occur on serpentine influenced soils and have been previously collected as N. intertexta, with which they are sympatric. However, they vary from N. intertexta subtly, yet consistently, in floral features and remarkably in surveyed DNA regions. Navarretia paradoxiclara and N. paradoxinota are sister species phylogenetically well separated from N. intertexta. With respect to each other, these new species are allopatric and diagnosable by differences in their corollas.